Immobilization of Palladium(II)acetate complex on dendrimer functionalized Cobalt ferrite nanoparticles as a nanocatalyst for Suzuki–Miyaura coupling and oxidation of sulfide - Atefeh Charabeh; Mohammad Piltan; Mohammad Ghadermazi (Scientific Reports)
Abstract A novel catalyst was prepared by the immobilization of Palladium(II)acetate complex on dendrimer functionalized magnetic nanoparticles. Using advanced characterization techniques, such as Transmission electron microscopies (TEM), Field emission scanning electron microscopy (SEM), Energy-dispersive X-ray spectrometer (EDS), Fourier transform infrared spectroscopy (FT-IR), Powder X-ray diffraction (XRD), Vibrating-sample magnetometer (VSM), Thermal gravimetric analysis (TGA), Inductively coupled Plasma (ICP) and Nitrogen adsorption desorption isotherm (BET) techniques. A thorough understanding of the catalyst structure and morphology was facilitated and confirmed its expected properties. The catalyst has been efficiently applied to Suzuki reactions and oxidation of sulfide. Its primary advantages include mild reaction conditions, high efficiency, and shorter reaction times than traditional methods. One of the greatest benefits of this catalyst is its reusability. It can be easily separated from the reaction mixture using a magnetic force and reused for up to five cycles without significant activity loss. This is important for sustainable chemistry, as it reduces waste and potentially lowers the costs.